2014
DOI: 10.3390/molecules19010595
|View full text |Cite
|
Sign up to set email alerts
|

The Human Telomere Sequence, (TTAGGG)4, in the Absence and Presence of Cosolutes: A Spectroscopic Investigation

Abstract: Abstract:Historically, biophysical studies of nucleic acids have been carried out under near ideal conditions, i.e., low buffer concentration (e.g., 10 mM phosphate), pH 7, low ionic strength (e.g., 100 mM) and, for optical studies, low concentrations of DNA (e.g., 1 × 10 −6 M). Although valuable structural and thermodynamic data have come out of these studies, the conditions, for the most, part, are inadequate to simulate realistic cellular conditions. The increasing interest in studying biomolecules under mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…4A) [35,36]. Although it is now assessed that this is mainly due to a preferential interaction of the polymer with a defined G4 conformation rather than to excluded volume effects, we used PEG 200 since it is one of the most used conformational transition inducer both on G4 and iM [37,38].…”
Section: Effect Of Ph or Peg 200 On The Non-canonical Structures Formmentioning
confidence: 99%
“…4A) [35,36]. Although it is now assessed that this is mainly due to a preferential interaction of the polymer with a defined G4 conformation rather than to excluded volume effects, we used PEG 200 since it is one of the most used conformational transition inducer both on G4 and iM [37,38].…”
Section: Effect Of Ph or Peg 200 On The Non-canonical Structures Formmentioning
confidence: 99%
“…Our group has been investigating the conformational properties of DNA oligomers with sequences related to the human telomere TTAGGG repeat. For these studies, we investigated the structure and stability of DNA sequences (XXXGGG) 4 , where X = A and/or T. In the presence of K + , these oligomers fold into intramolecular hybrid like quadruplexes possessing three G tetrads with loops in specific orientations in the folded structure. The results of spectroscopic studies indicated that changing the sequence context of the loops, even if just one base in any one loop, affected the structure and stability of the folded conformation. , …”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, characteristic intensity ratios of SERS bands originating from breathing vibrations of adenine and guanine rings indicated a non‐folded Tel24 structure in the absence of Na + ions and an anti‐parallel G‐quadruplex in presence of Na + ions 9,31 . CD spectra confirmed that enhancing silver nanoparticles did not affect the stability of either of the structures near the metallic surface 31,38,39 …”
Section: Resultsmentioning
confidence: 71%
“…Given that various G‐quadruplex forms are characterized by distinctive circular dichroism spectral signatures, CD spectroscopy has been widely used to monitor changes in the G‐quadruplex structures 38,39,42 . The results of our previous CD study indicated stable G‐quadruplexes adsorbed on the nanoparticles, not disturbed by weak interactions with the enhancing metallic surface 31 .…”
Section: Resultsmentioning
confidence: 95%